ANALYSING THE RELATIONSHIP BETWEEN DIURNAL ROAD TRAFFIC NOISE AND METEOROLOGICAL VARIABLES IN MAKURDI METROPOLIS, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
This paper explores the link between diurnal road traffic noise and meteorological variables based on an experimental study conducted in real traffic conditions in Makurdi metropolis during dry and wet seasons. Measurements of sound pressure level (LP), relative humidity, ambient temperature and wind speed were made at four locations of heavy traffic flow for forty days and the sound pressure level (LP) readings were used to compute the equivalent continuous noise level (Leq). Pearson correlation coefficient and Mann-Kendall trend tests were adopted to determine the relationship between equivalent continuous noise level (Leq) and the meteorological variables. The results revealed inconsistent trends across the different locations and seasons, with relative humidy exhibiting varying insignificant trends across the four locations and seasons with the only significant decreasing trend recorded at High Level Roundabout having a Kendall tau value of -0.6364 and R-value of -0.7315 during the wet season. The ambient temperature showed significant increasing trends at two locations and seasons and insignificant trends in the other locations, while wind speed recorded insignificant increasing trends across all locations except for SRS Junction which recorded a significant increasing trend during the wet season with a Kendall tau value of 0.5273 and R-value of 0.7498 which could be attributed to fluctuation in wind direction at the time of measurement of sound pressure levels. Notably, no consistent relationship was found between road traffic equivalent continuous noise levels and the meteorological variables. The study recommends implementing low-noise pavements and planting of ornamental trees and shrubs...
Keywords: Diurnal; Sound pressure level; Equivalent continuous noise level; Meteorological variables; Traffic flow